The Impact of Servant Leadership on Trust, Team Efficacy, and Intrinsic Motivation in Healthcare - Hayat, Salma; Wahab, Siti Norida; Othman, Norashida; Subramaniam, Nikram (Journal of Accounting, Business and Management (JABM), 2024)
This study aims to investigate the intricate dynamics of servant leadership and its impact on intrinsic motivation within the medical field, with a particular focus on the roles of trust as a moderator and team efficacy as a mediator. A sample of 200 hospital employees was surveyed using self-administered questionnaires. Data were analyzed using SmartPLS software to test the hypothesized relationships. The findings reveal that servant leadership significantly enhances intrinsic motivation, with trust amplifying this effect as a moderator, and team efficacy serving as a crucial mediator. Specifically, trust strengthens the relationship between servant leadership and team efficacy, which in turn, boosts intrinsic motivation. These results provide valuable insights into how servant leadership can be leveraged in healthcare settings to foster a motivated and effective workforce. The study addresses a critical gap in leadership literature by highlighting the dual roles of trust and team efficacy in the servant leadership process. The implications of this research suggest that healthcare organizations should focus on cultivating servant leadership qualities among their leaders, as well as fostering a trust-rich environment and promoting team efficacy to enhance employee motivation and overall performance.